Primary Intraosseous Synovial Sarcoma in the Mandible - Lucas Novaes Teixeira; Eduardo Zambaldi da Cruz; Ana Cláudia Garcia Rosa; Anderson Abdo Rodrigues; Fabrício Passador-Santos; Vera Cavalcanti de Araújo; Andresa Borges Soares (Case Reports in Oncological Medicine)
Synovial sarcoma (SS) is a rare malignant mesenchymal tumor that mainly occurs in body extremities, being uncommon in the head and neck region. In the present study, we described a case of primary intraosseous SS arising in the mandible of a 22-year-old young male. The patient reported a painful swelling on the left side of the mandible for the last 7 months. Imaging exams showed the presence of an expansive and multilocular radiolucent lesion, extending from the left condyle to the mandibular body. The clinic diagnostic hypotheses were ameloblastoma or malignant neoplasm. Histologically, the lesion was characterized by a proliferation of spindle cells exhibiting vesicular nuclei and evident nucleolus. Neoplastic cells were positive for AE1/AE3, cytokeratin 7, vimentin, CD-99, and TLE-1 and negative for CD-34, S-100, SMA, and HHF-35. A combination of clinical, histologic, and immunohistochemical characteristics supported the diagnosis of SS. The patient was referred for treatment, and preoperative exams did not reveal any other tumor foci in the body of the patient. The final diagnosis was of a primary intraosseous SS of the mandible.